Acute PR3-ANCA vasculitis in an asymptomatic COVID-19 teenager - Taylor Wintler; Monica Zherebtsov; Susanne Carmack; Rebecca Muntean; Sarah J. Hill (Elsevier, 2021)
We present the case of an acute onset ANCA positive vasculitis in an asymptomatic COVID-19 infected teenager, resulting in significant colonic damage. The patient was initially diagnosed with Henoch-Schönlein purpura and presented with worsening symptoms with significant necrosis of her perineum and rectum requiring surgical debridement and diverting colostomy. As a part of her work-up, she tested positive for COVID-19 total IgG/IgM antibodies and ANCA antibodies. This case complements previously reported cases of COVID-19 induced autoimmune disease in children but is novel in describing extensive intestinal disease as a result of an autoimmune vasculitis in a child.